Pediatric Heterotopic Gastric Mucosa of the Cervical Esophagus (Inlet Patch): Case Series with Clinical, Endoscopic, and Histopathological Correlation - Javier Arredondo Montero; Samuel Sáez Álvarez; Andrea Herreras Martínez; Ana Fernández-García; Cristina Iglesias Blázquez (Children, 2025)
Introduction: Inlet patch (IP) is a congenital anomaly characterized by gastric heterotopia in the cervical esophagus. While extensively described in adults, it remains poorl characterized in pediatric populations. Material and Methods: This retrospective, single-center study included all pediatric patients (0–14 years) diagnosed with IP between 2018 and 2025. Sociodemographic and clinical data were collected. A blinded pathologist assessed the presence and severity of inflammation within the IP. Results: Nine patients (median age, 12 years; range, 6–14 years) were included, with 78% beingmale. Cervical esophageal symptoms were identified in 67%, primarily dysphagia and gastroesophageal reflux disease-related complaints, although concomitant conditions such as eosinophilic esophagitis were frequently present. Three patients had symptoms potentially attributable to IP (33%). Endoscopic examination revealed characteristic well-demarcated salmon-red plaques in all patients, with multiple lesions observed in three cases. Histology confirmed gastric heterotopia with varying degrees of chronic inflammation in all cases. A potential association was observed between the severity of gastritis in the stomach, the severity of inflammation in the IP, and the presence of H. pylori, with 75% of patients with moderate-to-severe IP inflammation also exhibiting gastric H. pylori-associated gastritis. All patients except one received proton pump inhibitors, and symptoms improved in all cases. Conclusions: A thorough and targeted examination of the cervical esophagus significantly increased IP detection at our center, with most cases (89%) being diagnosed in the last 12 months. While mostly asymptomatic and incidental, IP can be symptomatic. In this case, series, we found a possible association between the severity of inflammation in the IP, the severity of gastritis, and the presence of H. pylori. Further studies are needed to define the clinical significance of pediatric IP and optimal management.